Pemanfaatan Grand Desain UIN Gusdur untuk Kemajuan Keilmuan Global dan Persoalan Kemanusiaan - Batsnah Nuwaifila (Sekolah Tinggi Ilmu Tarbiyah Bustanul Ulum Lampung Tengah, 2024)
When examining the history of science and religion, there are sacred texts that have been interpreted in a way that separates science and religion, leading to confusion in various fields at the time. This separation between science and religion arose due to misunderstandings in interpreting the universal teachings of Islam. Efforts to unify science and religion are currently being pursued, particularly in the field of education in Indonesia. This study employs a descriptive qualitative research method with a library research approach. The purpose of this study is to serve as a benchmark for educational institutions in developing their scientific knowledge in line with advancements inthe field of education. This research is important for the development of the Islamic State University KH. Abdurrahman Wahid in its pursuit of becoming a more advanced university. The result of this study is that the utilization of the grand design of UINGus Dur can be achieved through the dynamization of Islamic thought as an effort to reinterpret Islamic teachings in a way that allows for a more dynamic response to contemporary Islamic issues. In addition, the utilization of facilities and the development of curricula are necessary to improve the quality of education within the university.